Leadership and dynamic capabilities: the role of HR systems. Issue 2 (6th March 2017) - Lopez-Cabrales, Alvaro; Bornay-Barrachina, Mar; Diaz-Fernandez, Mirta
Abstract : Purpose: The purpose of this paper is to analyze the antecedents of the development of dynamic capabilities from an HRM perspective, considering the leading role of leadership styles and their potential impact on the orientation of HR systems and a firm's capabilities. Design/methodology/approach: The authors designed an empirical study of a sample of 107 Spanish industrial firms, asking HR, production and marketing managers to assess the CEO's leadership styles, the system of HRM practices applied in their organizations and dynamic capabilities. They applied multiple regressions and mediation analysis. Findings: The authors' results suggest that both transactional and transformational leadership styles are positively associated with dynamic capabilities (sensing, seizing and reconfiguration), directly and indirectly, through their effects on HR systems. Research limitations/implications: This paper approaches dynamic capabilities by using cross-sectional data. A longitudinal analysis would enrich this study. Also, the data aggregation in this paper does not allow to check different HR orientations from different departments. Finally, other HRM practices and strategic orientations could be assessed. Practical implications: This paper highlights the need to develop CEOs who are able to combine leadership behaviors in such a way that they promote HR systems (skill-based development vs job-based development) and to use them as mediating mechanisms and in order to generate greater dynamic capabilities in the organization. Originality/value: The authors are proposing that HRM can be applied to leverage a firm's competitive advantage, as HR systems mediate for obtaining different dynamic capabilities. Second, it could be concluded that any CEO should combine or display traits of both forms of leadership styles (transformational and transactional) in order to develop the full range of dynamic capabilities. Finally, this paper can provide some insights into the way dynamic capabilities can be measured and approached, through HRM microfoundations.